Studium optických a interferenčních jevů na tenkých vrstvách organických materiálů - Schmiedová, Veronika (Vysoké učení technické v Brně. Fakulta chemická, 2016)
Disertační práce je zaměřena na studium optických vlastností tenkých vrstev, stanovení jejich tlouštěk a disperzních závislostí indexu lomu. V první části jsou shrnuty teoretické poznatky o spektroskopické elipsometrii včetně charakterizace polarizace světla, stanovení fyzikálních vlastností a vyhodnocení experimentálních dat. Následuje experimentální a výsledková část, která se věnuje přípravě a charakterizaci tenkých vrstev studovaných materiálů: oxidu titaničitého (TiO2), nových organických materiálů (MDMO-PPV, PCDTBT, PCBTDPP, PC60BM, PC70BM) a redukovaného grafen oxidu (rGO), s ohledem pro jejich potenciální využití v organické fotovoltaice.

Ph.D. thesis is focused on the study and determination of layer thickness and optical properties, such as the dispersion dependence of the refractive index of various materials prepared in the form of thin layer. In the first part of this work the theoretical findings in the field of spectroscopic ellipsometry are summarised. These findings are followed by the description and characterization of the light polarization, evaluation of experimental data and determination of the physical properties of studied materials. Experimental and result section of this work is devoted to the preparation and characterization of thin films of the studied materials: titanum dioxide (TiO2), new organic materials (MDMO-PPV, PCDTBT, PCBTDPP, PC60BM, PC70BM) and reduced graphene oxide (rGO). These were all selected with respect to their potential use in the organic photovoltaics.
Study of Optical Properties and Interference Phenomena on Thin Films of Organic Mcaterials
Keywords: Organické materiály; anorganické materiály; tenké vrstvy; fotovoltaické články; optické vlastnosti; UV VIS spektroskopie; spektroskopická elipsometrie; Organic materials; anorganic materials; thin film layers; photovoltaic cells; optical properties; UV VIS spectroscopy; and spectroscopic ellipsometry